Effect of pH and Hypo-Osmotic Stress on NaCl Electrolyte Permeation across Red Blood Cell Membrane - B.O. Atolaiye; D.U. Edward-Ekpu; T.O. Bamidele (Journal of Applied Sciences and Environmental Management)
The study compares the effects produced by H+ concentrations in hypo-osmotically stressed NaCl solutions on permeation through RBC membrane. Iso-osmotic solutions of NaCl (160 mM) were prepared taking into account their molecular weight and osmotic concentration. Iso-osmotic solutions (25 mL) were diluted with 25 mL of distilled water to give half the initial concentrations (50 % hypotonic salt solutions). Hypotonic NaCl solutions of pH of 6.2, 6.8, 7.4 and 8.0 were prepared, mixed with 0.05 mL of RBC suspension and their absorbance/min for 16 min were measured using a UV/Visible spectrophotometer while the RBCs haemolyse. H+ concentration and hence pH was found to have a significant effect on ion permeability through RBC membrane. Permeation occurred faster in alkalinic solutions under hypo-osmotic stress. Permeation increased with every increase in pH and the increase is steeper at pH 7.4 – 8.0.